Respiratory Syncytial Virus Infection of Human Lung Fibroblasts Induces a Hyaluronan-Enriched Extracellular Matrix That Binds Mast Cells and Enhances Expression of Mast Cell Proteases - Reeves, Stephen R.; Barrow, Kaitlyn A.; Rich, Lucille M.; White, Maria P.; Shubin, Nicholas J.; Chan, Christina K.; Kang, Inkyung; Ziegler, Steven F.; Piliponsky, Adrian M.; Wight, Thomas N.; Debley, Jason S. (Frontiers in Immunology, 2020)
Human lung fibroblasts (HLFs) treated with the viral mimetic polyinosine-polycytidylic acid (poly I:C) form an extracellular matrix (ECM) enriched in hyaluronan (HA) that avidly binds monocytes and lymphocytes. Mast cells are important innate immune cells in both asthma and acute respiratory infections including respiratory syncytial virus (RSV); however, the effect of RSV on HA dependent mast cell adhesion and/or function is unknown. To determine if RSV infection of HLFs leads to the formation of a HA-enriched ECM that binds and enhances mast cell activity primary HLFs were infected with RSV for 48 h prior to leukocyte binding studies using a fluorescently labeled human mast cell line (LUVA). Parallel HLFs were harvested for characterization of HA production by ELISA and size exclusion chromatography. In separate experiments, HLFs were infected as above for 48 h prior to adding LUVA cells to HLF wells. Co-cultures were incubated for 48 h at which point media and cell pellets were collected for analysis. The role of the hyaladherin tumor necrosis factor-stimulated gene 6 (TSG-6) was also assessed using siRNA knockdown. RSV infection of primary HLFs for 48 h enhanced HA-dependent LUVA binding assessed by quantitative fluorescent microscopy. This coincided with increased HLF HA synthase (HAS) 2 and HAS3 expression and decreased hyaluronidase (HYAL) 2 expression leading to increased HA accumulation in the HLF cell layer and the presence of larger HA fragments. Separately, LUVAs co-cultured with RSV-infected HLFs for 48 h displayed enhanced production of the mast cell proteases, chymase, and tryptase. Pre-treatment with the HA inhibitor 4-methylumbelliferone (4-MU) and neutralizing antibodies to CD44 (HA receptor) decreased mast cell protease expression in co-cultured LUVAs implicating a direct role for HA. TSG-6 expression was increased over the 48-h infection. Inhibition of HLF TSG-6 expression by siRNA knockdown led to decreased LUVA binding suggesting an important role for this hyaladherin for LUVA adhesion in the setting of RSV infection. In summary, RSV infection of HLFs contributes to inflammation via HA-dependent mechanisms that enhance mast cell binding as well as mast cell protease expression via direct interactions with the ECM.